2009
DOI: 10.1248/bpb.32.688
|View full text |Cite|
|
Sign up to set email alerts
|

In Vitro Metabolism and Inhibitory Effects of Pranlukast in Human Liver Microsomes

Abstract: Cysteinyl leukotrienes (cysLTs) are 5-lipoxygenase pathway products of arachidonate that induce bronchoconstriction, vascular hyperpermeability, mucosal edema accumulation, and mucus secretion. [1][2][3] Pranlukast is a selective cysLTs receptor antagonist, and a 225 mg twice-daily dose has been used to treat bronchial asthma and allergic rhinitis in Japan.The absorption fraction of pranlukast in human is approximately 20%, based on the excretion ratio of the unchanged form in the feces following oral administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, it helps establish the degradation pathway and the mechanism of formation of a DP. It also helps elucidate the intrinsic stability of the molecule. , The knowledge of the drug’s DPs can help decrease the toxicity and side effects of the drug. Hence, the complete characterization of DPs is mandatory .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it helps establish the degradation pathway and the mechanism of formation of a DP. It also helps elucidate the intrinsic stability of the molecule. , The knowledge of the drug’s DPs can help decrease the toxicity and side effects of the drug. Hence, the complete characterization of DPs is mandatory .…”
Section: Introductionmentioning
confidence: 99%
“…One stability-indicating reverse-phase high-performance liquid chromatography (RP-HPLC) method has reported . Few RP-HPLC methods have reported of PRN in formulation, PRN and its metabolism in plasma, , PRN pharmacokinetics in plasma, and few LC–MS/MS (liquid chromatography–tandem mass spectrometry) methods have reported for PRN in plasma. ,, But no studies are available for the isolation and characterization of the stress DPs of this drug. Hence, the study aims to develop and validate a novel stability-indicating liquid chromatography–electrospray ionization–quadrupole time of flight tandem mass spectrometry (LC-ESI-QTOF-MS/MS) method for the determination of PRN along with isolation, in vitro and in silico toxicity study of major DPs of PRN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Focusing on the metabolism of pranlukast, the studies performed so far have shown that biotransformation reactions occur on the side chains instead of the chromone core. 7 The relevance of the chromone scaffold in medicinal chemistry has been an up-and-coming area of study. Publications on chromone-based compounds have been increasingly acknowledged, a process driven by recent progress in development of chromone-based drug candidates.…”
Section: Introductionmentioning
confidence: 99%
“…They have been used since ancient times in traditional medicine and are well-known by their diversity of pharmacological properties, such as antiallergic, anti-inflammatory, antidiabetic, antitumor, and antimicrobial. , Moreover, the use of chromone-based drugs in the therapy of asthma has been extensively explored, mainly as bronchodilators. , The drug discovery processes have culminated in the development of disodium cromoglycate (DSCG) and pranlukast (Figure ), which are useful drugs for the treatment of mild to moderate asthma and allergic rhinitis, respectively . Focusing on the metabolism of pranlukast, the studies performed so far have shown that biotransformation reactions occur on the side chains instead of the chromone core …”
Section: Introductionmentioning
confidence: 99%